Potential antioxidant and anti-inflammatory activities of Thai plai (Zingiber cassumunar Roxb.) essential oil - D. Leelarungrayub (2018)
The aims of this study were to evaluate the in vitro antioxidant and anti-inflammatory actions of essential oils of plai (Zingiber cassumunar Roxb.) compared to eucalyptus (Eucalyptus globulus Labill.) and lime (Citrus aurantifolia Swing.). The antioxidant activities of the essential oils were determined through an ABTS cation radical decolorisation assay and measuring scavenging H2O2 in a monocyte cell line (U937) with DCFH-acetate. The anti-inflammatory activity was assayed in a lipopolysaccharide-activated macrophage cell line (J744), in which nitric oxide and COX II levels were determined by Griess reagent and an ELISA kit. Plai essential oil had the highest antioxidant activity (11.46 ± 0.72 mmol Trolox/ml oil) on scavenging the ABTS cation radical, followed by eucalyptus (9.30 ± 2.20 mmol Trolox/ml oil) and lime (0.00 ± 0.58 mmol Trolox/ ml oil) oils. Plai essential oil also displayed activity on scavenging H2O2 generated by ultrasound exposure (3.0 W/cm 2, continuous mode, 20 min). Dilutions of 1:2,000 and 1:1,000 (v:v) of plai oil demonstrated H2O2 scavenging activity by reducing emissions of DCFH-fluorescence within U937 cells, compared with the cell control. Plai essential oil inhibited nitric oxide (NO) production at 1:100 (v:v) (24.20 ± 1.42 μmol/l) and 1:1,000 (v:v) (28.56 ± 3.8 μmol/l) in the macrophage cell line (J774), compared with untreated cells (35 ± 5.2 μmol/l). However, high concentrations of plai oil (1:1 and 1:10), were toxic to U937 and J744 cell lines. Additionally, plai oil at dilutions of 1:1,000 and 1:2,000, significantly inhibited COX II activity in treated cells (42 ± 0.2% inhibition) compared to the untreated cells (22 ± 0.3% inhibition). Three major compounds of plai essential oil, namely sabinene (18.79%), terpinen-4-ol (48.17%) and (E)-I-(3,4-dimethyoxyphenyl) butadiene (15.09%), were determined by GC/MS analysis. © Essential Oil Resource Consultants. All rights reserved.